CAPUNG SEBAGAI TITIK TOLAK PENCIPTAAN KARYA SENI GRAFIS MELALUI TEKNIK SERIGRAFI - EKO RAMDI FAUZI, Yofita Sandra, S.Pd., M.Pd, Drs. Yusron Wikarya, M. Pd (Serupa The Journal of Art Education, 2014)
This creation aimed to visualize the beauty of the body's anatomical shape, color, nature, and behavior of dragonflies in life. In addition, it this creation aimed to refer back meanings and uniqueness properties owned by the dragonfly. Trace dragonfly as insects provided many benefits for other living creatures. Dragonflies have a life style, nature and characteristics of positive meaningful and benefitto many people, both economically and aesthetically. While the techniques or methods used in making of this thesis was the technique of serigraphy, which is a technique that is produced from silk stretch open the field of mold is then filtered using a squeegee made of rubber as a tool to remove the ink from screen to print areas.After conducting a series of lengthy creation process, it created ten graphic artwork with serigraphy technique on canvas, including: 1) Contrary Rear, 2) Protector, 3) The day of Twilight, 4) Marriage Dragonflies, 5) Options and Risk, 6) bound and Free, 7) Victorious, 8) Mutual bound, 9) Moving Forward, 10) Toward Focusing. Through graphic artwork with the theme of this dragonfly life, students of visual art were expected to create new works of art. After seeing the work better of authors, collegean can evoke their spirit of the work of art, that can be use as a reference to make better graphic artworks in the future.Keyword: Dragonfly, Creation, Graphic, Serigraphy